Microbial biomass and maize nitrogen uptake under a Psophocarpus palsustris live mulch grown on a tropical Alfisol - Mulongoy, K. (1986)
Nitrogen uptake by maize was monitored for five cropping seasons in a live-mulch of Psophocarpus palustris (psopho) established on an Alfisol at the International Institute of Tropical Agriculture, Ibadan, Nigeria. During the first four cropping seasons, psopho and maize competed for soil N in the live-mulch, and maize grown in a psopho live-mulch contained less N than maize grown by itself. In the fifth season, psopho contributed 15 kg N ha−1 to maize in the psopho-maize plots that were cropped continuously for five seasons. Maize grown in a psopho live-mulch that had already been established for four cropping seasons contained 36 kg ha−1 more N than maize grown by itself. This positive N contribution came, at least in part, from increases in microbial biomass and in organic matter derived from the cover crop in the form of litter and earthworm casts. These casts represented a supplementary N reserve of 13–21 kg ha−1 under the cover crop. The casts also had a larger biomass C content, and higher percent stress-labile N (PSN), organic C and total N than the corresponding soils. Biomass C and PSN values were the lowest in soils from bare maize plots, indicating that the live-mulch improved soil nutrient availability and biological properties.